An in-depth study on students’ perceptions of key factors influencing their willingness to communicate in EFL classrooms - Afifah Marshalina (PT. MAWAMEDIA JAYAMUSTA BUANASIHA, 2025)
Communicative competence has become a primary objective in second and foreign language education. A crucial component of achieving this competence is learners’ Willingness to Communicate (WTC) in the target language. This study aims to explore the perceptions of students regarding the factors that influence their WTC in English as a Foreign Language (EFL) classrooms. The main objective is to identify and analyze internal and external elements that contribute to students' decisions to engage in classroom communication using English. This research employed a qualitative case study design to gain deep insights into the subject matter. Two secondary school students were purposefully selected as participants based on contrasting backgrounds in English language exposure. One participant had extensive experience and exposure to English since early childhood, while the other had limited exposure and began learning English more recently. This purposeful sampling allowed the researcher to gather diverse and detailed perspectives. Data were collected through semi-structured interviews to elicit rich, open-ended responses. The interviews were then transcribed and analyzed using thematic analysis to identify recurring patterns and themes related to WTC. The analysis revealed several key factors influencing students’ WTC, including affective elements (such as confidence and anxiety), the classroom environment, linguistic competence, the nature of classroom tasks, and the teacher’s role and encouragement. The findings suggest that WTC in EFL settings is shaped by a combination of personal, social, and instructional dynamics. Students are more inclined to communicate when they feel emotionally secure, supported by their peers and teachers, and when the learning environment promotes engagement. The study concludes that fostering a positive emotional and instructional environment is essential for increasing WTC. The research highlights the importance of teacher sensitivity to student needs and recommends further studies involving more participants to enhance generalizability and explore additional influencing factors.